The Impact of Adherence to the Dimensions of Entrepreneurial Orientation on the Performance of Projects Small and Medium A Field Study in Lattakia Governorate - عيسى يارا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to determine the extent to which the owners of small and medium enterprises adhere to the dimensions of the entrepreneurial orientation (independence, creativity, risk-taking, and proactivity), and the impact of this on the success of their projects, and thus draw their attention and direct them to the need for an entrepreneurial approach in their projects to ensure improvement in their performance and continuity. The research relied on the descriptive method, and the study population consisted of all managers or owners of small and medium enterprises in Lattakia Governorate, where the researcher drew a simple random sample of managers or owners of these projects, and the sample size was (60) managers or owners of a project, distributed among projects service and industrial projects, where the questionnaire "research tool" was distributed to them, and (52) complete and valid questionnaires were retrieved for statistical analysis, with a response rate of (86.67%). The results of the research showed that there is a direct and strong significant significant effect of the entrepreneurial orientation dimensions (independence, creativity, risk tolerance, and proactivity) on the performance of small and medium enterprises. Creativity comes in second place, after autonomy in third place, after taking risks in fourth place.